A Selection of Phaseolus Vulgaris Bean Varieties to Explore Their Nutritional Quality from the Dawn of Creation to the Science and Technology of the Modern World - Robijaona Rahelivololoniaina B. (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The Malagasy Phaseolus vulgaris L varieties analyzed in this study showed the presence of high nutritional elements, particularly protein levels of 20.3899%; 21.3130%; 20.6173%; 23.0134%; 21. 7245%; 21.3049% respectively for the six varieties 55(B), RI 5-2, CAL 98, Ran'omby 1, RI 5-3, Ran'omby 4, as well as carbohydrate contents ranging from 57.4657% for Ran'omby 1 to 65.1171% DM for CAL 98. The presence of essential mineral elements for human nutrition (iron, zinc, magnesium, calcium, potassium, sodium, phosphorus...) and phytochemical families reveal its virtues as a food. This means that Phaseolus vulgaris L is a complete human food.